Sistema web basado en inteligencia de negocios para el control de combustible en los vehículos de la empresa Brunner 2024 - Poblete Ramirez, Carlos Enrique (2025)
Until recently, at Brunner S.A.C, fuel tracking and management were done manually, causing delays and increasing costs due to lack of control and theft risks. Nowadays, automated systems are in place that facilitate fuel management using statistical technologies and business intelligence, allowing for more efficient management. This study focused on implementing a Business Intelligence-based web platform to optimize fuel management at Brunner S.A.C. The primary objective was to improve sensor data collection and analysis through dashboards, detecting fuel theft early and monitoring each vehicle's route for more rational fuel use. The research question was: To what extent could fuel control in Brunner's vehicles be improved with a Business Intelligence web application? The general hypothesis was that "Fuel control in Brunner's vehicles would significantly improve with this web platform." The overall objective was to enhance fuel control at Brunner S.A.C through an advanced Business Intelligence web system, with specific objectives such as evaluating sensor data acquisition time, fuel report generation efficiency, and measuring user satisfaction with the system. To validate the hypotheses and achieve the objectives, statistical methods like t Student and U. Mann Whitney tests were applied, tailored to the numerical and categorical variables of the study.